1997
DOI: 10.1073/pnas.94.21.11205
|View full text |Cite
|
Sign up to set email alerts
|

Cockayne syndrome group B protein enhances elongation by RNA polymerase II

Abstract: Cockayne syndrome (CS) is characterized by impaired physical and mental development. Two complementation groups, CSA and CSB, have been identified. Here we report that the CSB gene product enhances elongation by RNA polymerase II. CSB stimulated the rate of elongation on an undamaged template by a factor of about 3. A thyminethymine cyclobutane dimer located in the template strand is known to be a strong block to transcription. Addition of CSB to the blocked polymerase resulted in addition of one nucleotide to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
186
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(201 citation statements)
references
References 35 publications
11
186
1
3
Order By: Relevance
“…Besides the defect in coping with many types of DNA damaging agents, CSB cells have markedly reduced transcription (Balajee et al, 1997;Dianov et al, 1997). CSB stimulates transcription by stimulating elongation of actively transcribing RNA polymerase bound to DNA and nascent RNA (Selby and Sancar, 1997a;Tantin et al, 1997;. Furthermore, using array analysis, Kyng et al (Kyng et al, 2003) demonstrated that the transcriptional response after oxidative stress is defective in CSB cells.…”
Section: The Role Of Csb In Various Cellular Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the defect in coping with many types of DNA damaging agents, CSB cells have markedly reduced transcription (Balajee et al, 1997;Dianov et al, 1997). CSB stimulates transcription by stimulating elongation of actively transcribing RNA polymerase bound to DNA and nascent RNA (Selby and Sancar, 1997a;Tantin et al, 1997;. Furthermore, using array analysis, Kyng et al (Kyng et al, 2003) demonstrated that the transcriptional response after oxidative stress is defective in CSB cells.…”
Section: The Role Of Csb In Various Cellular Processesmentioning
confidence: 99%
“…In vivo transcription in CSB deficient cells have been reported to be 50% of wild type cells and in vitro transcription studies on chromatin from CSB deficient cells found that transcription elongation was significantly decreased in the absence of CSB (Selby and Sancar, 1997a). When compared to CSB deficient cells, the transcription from chromatin in wild type cells was more resistant to the detergent Triton X-100, indicating that the transcription machinery is less tightly associated with chromatin in CSB deficient cells compared to wild type cells (Balajee et al, 1997).…”
Section: Csb and Chromatin Structurementioning
confidence: 99%
“…Rather, it appears that the severe photoreceptor loss in Csb m/m animals represents a CS-specific trait related to a function of the CSB protein outside the context of NER. The nature of this non-NER function is not yet clear, but there are indications that the CSB protein has an auxiliary function in transcription elongation, notably the bypass of pause sites and RNA secondary structures (3,18,30,42), as well as in the repair of other (non-NER-type) oxidative DNA lesions (16,17,39,43 (43) recently showed that plasmids containing 8-oxoG are less well repaired by CS patient cells, whereas strand breaks (as also produced by ionizing radiation) are repaired at a normal rate. Furthermore, Csb m/m mice are sensitive to the pro-oxidant di-(2-ethylhexyl)phthalate, and exposed animals contain higher levels of 8-oxoG in the liver than wt mice (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The CS-specific features may be attributed to other roles of CSA and CSB proteins, outside the context of NER. There are indications that these proteins are involved in transcription elongation (3,18,30,42) and in the repair of other, non-NER types of DNA damage, e.g., oxidative DNA lesions (15-17, 39, 43, 45).…”
mentioning
confidence: 99%
“…The first class is composed of members of the SII family. 3,5 The second class comprises a collection of elongation factors, including TFIIF, 6 Elongin, 7,8 ELL 9 and CSB, 10 which increase the overall rate of mRNA chain elongation by decreasing the frequency and/or duration of transient pausing of pol II at sites along the DNA template.…”
mentioning
confidence: 99%